Europäisches Zivilprozessrecht Einfluss auf Deutschland und Ungarn - Ahrens, Martin; Lipp, Volker; Varga, István (Universitätsverlag Göttingen, 2011)
The Europeanisation of civil procedure has moved from slogan to reality. Nevertheless, the European Union does not have its own civil jurisdiction. Therefore the national codes of civil procedure are facing enormous challenges by the increasing access of the European legislator on the law of civil procedure. These challenges have been part of intensive discussions on several research conferences at the Georg-August- University Göttingen and the Eötvös-Lorand-University Budapest. They were focused on the interactions between European Law and the quite different traditions of national codes of civil procedure.